English Vocabularies Acquisition in International Class of Elementary School Diniyyah Al-Azhar Jambi - dwi rizki anggraini; alfian alfian; ulfatmi azlan (English Literature Department, Adab and Humanities Faculty, 2020)
Nowadays, English is known as an international language and becomes a foreign language that is very popular to be mastered by Indonesian as a second language. The implementation of English as a second language in Indonesia is not only acquired by adults but also by children. A lot of research about second language acquisition has been done, but the research about second language acquisition for children is still limited in UIN Sulthan Thaha Saifuddin Jambi. The aims of this research are: (1) to find out the English vocabularies acquired by Al Azhar students, (2) to find out the stages of second language process acquired by Al Azhar students, and (3) to find out the factors that influence Al Azhar students to acquire the second language. This research uses qualitative research with the descriptive method and uses class of word theory by Daniel Jurafsky and James H. Martin, stages of second language theory by Stephen Krashen, and the factors influence of second language acquisition theory by Abdul Chaer. Observation, interview, and documentation techniques are used for collecting the data. The descriptive analysis technique is used for analyzing the data. The results for this research indicate that: (1) the students already acquired some of vocabularies that belong to noun, pronoun, adjective, verb, adverb, conjunction, and preposition, but noun is the most dominant class of word which children acquired, (2) from four stages the students passed two stages of second language acquisition they are: pre-production and early production, and (3) the students have three motivations in acquiring the second language they are motivation factors, formal presentation factors, and environment factors.